Assessment of Instructional Resources for Teaching Basic Technology in Junior Secondary Schools in Ogbomoso, Nigeria - Olarinde, L. A.; Fakomogbon, M. A.; Olabisi, A.; Adetunde, I. (IJRDO- Journal of Educational Research, 2017)
This study assessed instructional resources for teaching Basic Technology in Junior Secondary Schools in Ogbomoso, Nigeria. Specifically, the study assessed the available non- human resources (workshops, hand tools, machines, audio-visuals and visuals) that are used for teaching Basic Technology. The researchers also made attempt to find out the functionality of the available resources, it’s frequency of use and their adequacy to the recommendation of NERDC (2007). The research sample consisted all the 75 junior secondary schools of both private and public schools in Ogbomoso (Ogbomoso South and North, Local Government Areas). The instrument used was a researcherdesigned questionnaire named ‘Availability and utilization of instructional resources in Teaching Basic Technology consisting three (3) sections (A, B, & C). The questionnaire was administered, while frequency count and percentages were used as statistical method to answer research questions. The result of the analysis was as follows: 39 (52.0%) workshops, 60 (5.3%) machines, 310 (9.8%) audiovisuals, 1,756 (15.6%) hand tools and 1,422 (63.2%) visuals were available in all the sampled schools in Ogbomoso. The data on functionality revealed that 5.2% - 26.7% of the available resources were functioning which means that the practical aspects of the subject were thoroughly taken care of. The findings also showed that only three (3) out of the twenty-six (26) items used, met the recommendation of the NERDC 2007. Finally, the analyzed results showed that from all the available resources; 26.7% of workshops, 32.3% hand tools, 5% machines, 16.8% audio-visuals and 74% visuals were frequently used in the sampled schools.